ANALISIS PEMBUATAN SISTEM ANTIFRAUD PADA STARTUP FINTECH, KHUSUSNYA PEER-TO-PEER LENDING - Andre Pratama Adiwijaya; Wisnu Sukma Maulana (Jurnal Ilmiah Teknik, 2023)
Fintech startups, especially those in the peer-to-peer lending model, have major challenges regarding security risks and fraud. Therefore, this research aims to analyze the creation of an effective antifraud system to increase transaction security on peer-to-peer lending platforms. By understanding the characteristics of possible fraud and applying advanced technology, it is hoped that this system can provide better protection against security risks.